Regulatory experience of TOPS: an internet-based system to prevent healthy subjects from over-volunteering for UK clinical trials. - Allen, C.; Francis, G.; Martin, J.; Boyce, M. (European Journal of Clinical Pharmacology, 2017)
Purpose: The aim was to review the use of The Over-volunteering Prevention System (TOPS) since the HRA began hosting it in 2013, and the Medicines and Healthcare products Regulatory Agency (MHRA) experience of monitoring its use by UK clinical research units. Methods: The HRA searched the TOPS database for the number, type and location of units and the number of entries. The MHRA inspectors reviewed their findings from routine inspections. Results: Twenty-two additional UK units registered to use TOPS during 2013-2016, making a total of 84 units since TOPS was established in 2002. Use of TOPS is now a condition of research ethics committee approval of a phase 1 study and fulfils MHRA accreditation requirements for preventing over-volunteering. The total number of entries by all active units during 2013-2016 was 89,335, of which 84% were UK citizens and 16% non-UK citizens. The total number of entries during 2002-2016 was 249,612. Only 15 of 24,531 subjects (1/1600) and 18 of 18,745 subjects (1/1040) entered in 2015 and 2016, respectively, were deemed potential over-volunteers. Conclusions: The findings continue to support the concept that TOPS not only helps to prevent over-volunteering, but also deters subjects from trying to do so. Regulation of TOPS by the HRA and MHRA has enhanced its effectiveness, benefited all users and helped to improve the safety of volunteers who participate in non-therapeutic trials in the UK. The UK is still the only country with a national database to prevent over-volunteering that has published data on its widespread use and effectiveness.